2017
DOI: 10.1021/acsenergylett.7b00222
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Chemical Tuning of High-Energy-Density Metal Oxides for Lithium Ion Battery Electrode Applications

Abstract: Metal oxides represent a set of promising materials for use as electrodes within lithium ion batteries, but unfortunately, these tend to suffer from limitations associated with poor ionic and electron conductivity as well as low cycling performance. Hence, to achieve the goal of creating economical, relatively less toxic, thermally stable, and simultaneously high-energy-density electrode materials, we have put forth a number of targeted strategies, aimed at rationally improving upon electrochemical performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 53 publications
0
36
0
Order By: Relevance
“…Topography information and the surface current distributions of MoO 3− x and Cu 2 O@MoO 3− x nanobelts were obtained. Current–voltage ( I – V ) measurements (Figure S11d,h, Supporting Information) indicated that the current through the MoO 3− x nanobelts was lower than the current through Cu 2 O@MoO 3− x at both polarities of voltage applied in the range up to 14 V. Although MoO 3− x and Cu 2 O do not corporate with each other, the existence of Cu 2 O particles on the surfaces of the MoO 3− x nanobelts enhances the electrical conductivity of the electrodes …”
Section: Resultsmentioning
confidence: 99%
“…Topography information and the surface current distributions of MoO 3− x and Cu 2 O@MoO 3− x nanobelts were obtained. Current–voltage ( I – V ) measurements (Figure S11d,h, Supporting Information) indicated that the current through the MoO 3− x nanobelts was lower than the current through Cu 2 O@MoO 3− x at both polarities of voltage applied in the range up to 14 V. Although MoO 3− x and Cu 2 O do not corporate with each other, the existence of Cu 2 O particles on the surfaces of the MoO 3− x nanobelts enhances the electrical conductivity of the electrodes …”
Section: Resultsmentioning
confidence: 99%
“…LIBs function by a conceptually simple electrochemical process consisting of the extraction and insertion of Li + between two electrodes with simultaneous removal and addition of electrons to store or release electrical energy . However, the performance of LIBs depends strongly on the electrode materials and their interaction with the electrolyte . Although many high capacity LIB negative electrode materials are available including Si, Ge, and Sn, they cannot be used in bulk form due to their low range of operating voltage, high stress generated by intercalation of Li + , and the consumption of Li + by unstable solid‐electrolyte interface layers during cycling …”
Section: Introductionmentioning
confidence: 99%
“…The computational chemistry provides suitable ways for chemical researchers until they can search and discover the effective anode materials to use in batteries. [17][18][19][20][21][22][23] The computational chemistry tools provide insights into the cell voltage and capacity of metal-ion batteries and can use to predict and compare the efficiency and performances of proposed new batteries. The computational chemistry is predicate, calculate and provide the electrochemical properties of various materials.…”
Section: Introductionmentioning
confidence: 99%